1998
DOI: 10.1111/j.1463-6409.1998.tb00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaspidacea, Bathynellacea (Crustacea, Syncarida), generalised tracks, and the biogeographical relationships of South America

Abstract: The spatial evolution of South American Syncarida (Anaspidacea and Bathynellacea) and related taxa is evaluated applying a panbiogeographic approach, where Ocean basins are used to identify major patterns of intercontinental distribution. The Pacific basin, corresponding to a southern temperate track, is identified as the major evolutionary centre for Stygocaris(Stygocarididae), Bathynella (Bathynellidae), Atopobathynellu, and Chilibathynella (Parabathynellidae), whereas distribution of Nannobathynella (Bathyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Two cladistic biogeographic analyses based on plant, fungal, and animal taxa, including Coleoptera, Diptera, Ephemeroptera, Hemiptera, and Mecoptera (19, 151), showed that South America is a composite area because southern South America is more closely related to the southern temperate areas that correspond to the Austral kingdom, whereas tropical South America is more closely related to Africa and North America. Other cladistic and panbiogeographic studies (18,48,65,78,113) also support the hypothesis that South America is a composite area, with the Andean region closely related to the southern temperate areas and the Neotropical region closely related to the Old World tropics. Other authors have addressed the dual nature of South America (20,51,53).…”
Section: Andean Regionmentioning
confidence: 66%
“…Two cladistic biogeographic analyses based on plant, fungal, and animal taxa, including Coleoptera, Diptera, Ephemeroptera, Hemiptera, and Mecoptera (19, 151), showed that South America is a composite area because southern South America is more closely related to the southern temperate areas that correspond to the Austral kingdom, whereas tropical South America is more closely related to Africa and North America. Other cladistic and panbiogeographic studies (18,48,65,78,113) also support the hypothesis that South America is a composite area, with the Andean region closely related to the southern temperate areas and the Neotropical region closely related to the Old World tropics. Other authors have addressed the dual nature of South America (20,51,53).…”
Section: Andean Regionmentioning
confidence: 66%
“…Better studied are some smaller invertebrate taxa from the subterranean realms, where the Anaspidacea and the Bathynellacea (Crustacea: Syncarida) provide perhaps the best examples of strong disjunctions between southern South America on one side and south-eastern Australia and New Zealand on the other, explained by the Gondwanan transantarctic dispersal scenario (e.g. Stygocaris Noodt, 1963, Atopobathynella Schminke, 1973, Chilibathynella Noodt, 1963 (Schminke, 1974;Lopretto and Morrone, 1998). In the Rotifera, the distribution pattern remains unstudied even though this old group shows typical Gondwana-type disjunctions (e.g.…”
Section: Amphi-and Trans-pacific Disjunctions In Aquatic Invertebratesmentioning
confidence: 99%
“…Further these Gondwanan links between the major continents (e.g. the 'cosmopolitan' Bathynellacea (Lopretto and Morrone 1998)) are likely to be an indicator of new regions of subterranean faunal significance. To date, Africa remains largely unexplored, apart from the Mediterranean north coast and Atlas Mountains.…”
Section: Possible Subterranean Biodiversity Hotspots Elsewhere In Thementioning
confidence: 99%